Pushing out towards the limits, and finding the centre: the mystical vision in the work of Ursula K. Le Guin - Hoyle, Gisela Beate (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 1992)
This thesis explores the major novels of science fiction and fantasy writer, Ursula K. Le Guin: it follows her journey from her first imaginary country, Orsinia, through the inner lands of Earthsea and the outer spaces of the Hainish Ekumen to her Yin utopia in a future California and an Earthsea revisited. In each of these worlds she moves towards an experience of an inner, unified truth which is comparable to the ecstatic experience of the religious mystics and that of which T.S Eliot writes in his Four Quartets. Through her reading of the Taoist sages and the discovery of their perception of Life as a constant and ongoing process rather than as a series of isolated events or states, whether mystical or mundane, these worlds and planets become symbols of a way of life instead of static objects. In her medium, narrative, this way is embodied in the story: the movement towards that moment of enlightenment, which is revealed as the heart, the life-giving centre of each world. It is the home to which each journey returns. "True voyage is return' (The Dispossessed). Owing to this perception of the immanent (w)holiness of life, of the many, different realities, she moves from a serene Taoist equilibrium to an angry feminist rejection of the masculine, dualist, Western civilisation, in which Man has largely been perceived as a creature apart; apart from nature, a guest on this planet, belonging to another world. In her anarchist and feminist utopias she seeks a new spititual home, a less alienated identity for humankind. Despite this apparent "development", at the heart of aU her books there is that same joy in this, mortal life, the search for which she sees as the most essential of aU human pursuits. That, ultimately, is both source and subject of Le Guin's work; and each new world explored is a different manifestation of the joyful Tao, a celebration of life.
Keywords: Le Guin, Ursula K., 1929- -- Criticism and interpretation; Mysticism in literature